Attentional focus strategies in racket sports: A systematic review. - Marcin Starzak; Tomasz Niźnikowski; Michał Biegajło; Marta Nogal; Weronika Łuba Arnista; Andrzej Mastalerz; Anna Starzak (PLoS ONE)
The body of evidence has shown that the external focus of attention (EF) rather than the internal focus of attention (IF) enhances motor skill learning and performance. Within racket sports which require a high level of motor control, anticipation skills, and mental preparedness, effectively directing attention is essential to elicit improvements in athletic performance. The present review aimed to evaluate the scientific evidence concerning the effects of attentional focus instructions on motor learning and performance in racket sports. We systematically reviewed the literature according to the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. The study was registered with the Open Science Framework (osf.io/m4zat). Four electronic databases (Web of Science, Scopus, MEDLINE, and SPORTDiscus) were searched for original research publications. Inclusion criteria were: peer-reviewed journals; healthy and free from injury participants; attentional focus literature specific to the external or internal focus; attentional focus related to motor learning or motor performance; studies included at least one comparator (e.g., different attentional focus group, or control groups with neutral or no specific instruction); publications in which task(s) or skill(s) related to one of the racket sports (tennis, table tennis, badminton, squash, or padel). The initial search yielded 2005 studies. Finally, 9 studies were included in the quantitative analysis. Overall, the results indicated that EF benefits the learning and performance of racket sport skills, compared to IF and over control conditions. The findings suggest that coaches and practitioners should consider the adoption of EF to optimize racket skills performance, particularly in novice or low-skilled athletes.